Elderly empowerment with evidence-based depression problems using an android application - Sahar, Junaiti; Permatasari, Henny; Pradana, Anung Ahadi; Balqis, Ummi Malikal (Community Empowerment, 2021)
Psychosocial problems in the elderly are a quite common health problem in this decade. Changes in the elderly related to psychosocial problems include changes in mental status, ability in decision making, affective function, conflict with reality and social support. This evidence-based community service activity consists of health promotion of depression in the elderly, education on depression screening using Depression, Anxiety, Stress Scale (DASS) tools, and socialization and implementation of the Depression-Aware Elderly Group. The activity was held in Mekarjaya Village, Depok in September-November 2020 and was attended by 42 elderly and cadres. Based on the measurement results, it was concluded that there was an increase in people's understanding of the depression condition experienced by the elderly where the mean value before the intervention was 0.46, increasing to 3.21 after the intervention. Other than that, the problem of depression in the elderly needs to be considered by the government and becomes one of the priority programs.